Berkebun Sayur dengan Teknik Vertikultur sebagai Upaya Peningkatan Ketahanan Pangan Santri Panti Asuhan Jatibening Bekasi - Sri Rahayu; Dian Ekawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The level of vegetable consumption in Indonesia is shallow compared to the standards that have been set. Various factors contributed to the low rate of vegetable consumption, including economic factors and knowledge. Most of the santri at the orphanage in Jatibening consume fewer vegetables due to lack of knowledge and economic reasons. All students in this orphanage come from underprivileged groups, whereas since 2012, the orphanage has not received subsidies from the government for its operations. This activity aims to provide knowledge and skills for students at the Al Hidayah orphanage and provide vegetable plant verticulture to improve the students' food security. The method approach used is the active community participation (PAM) method in which the community is directly involved in activities. The pretest method stages, providing material, post-test, demonstration of making vegetable plant verticulture and redemonstration by students. The plants cultivated are mustard greens, spinach, and bean sprouts. The activity was held at the Al Hidayah Jati Bening orphanage on Sunday, 1 October 2017. This activity was attended by 20 participants from the Al Hidayah and Roisul Falah Jatibening orphanage Bekasi. Based on the pre-test and post-test results, it was obtained an increase in knowledge of 72.43%. It can be concluded that there is an increase in knowledge about verticulture and skills in making vegetable plant verticulture as demonstrated. This activity resulted in verticulture at the Al Hidayah orphanage that could be used by students at the orphanage to meet the need for vegetables.